Calculation of Thickness of Midship Construction Plates According to the Ship Classification Board - Amran, Andi Ana Humaerah; Shidik Burhani; Nur Aulia (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This research aims to find similarities in principles, basic calculations and construction calculation results according to the DNV, RINA and BKI classification bodies, so that the research results can be used by ship owners in choosing the appropriate classification body for their ships. Comparisons were made on Midship construction using the method of tabulating formulas for determining structural dimensions by each classification. In terms of the conditions for using the rules, they are differentiated based on the conditions of the water object, the length of the ship and the construction system object used. The calculation results show that BKI tends to have a larger plate thickness but a smaller modulus, while DNV tends to have a thinner plate but a larger modulus. Ease of reading the rules, in this case DNV has rules that are more "User Friendly" than the other two classification bodies